Red blood cell depletion from bone marrow and peripheral blood buffy coat: a comparison of two new and three established technologies. Issue 6 (2nd February 2015) - Sorg, Nadine; Poppe, Carolin; Bunos, Milica; Wingenfeld, Eva; Hümmer, Christiane; Krämer, Ariane; Stock, Belinda; Seifried, Erhard; Bonig, Halvard
<x xml:space="preserve">Abstract</x> BACKGROUND Red blood cell (RBC) depletion is a standard technique for preparation of ABO‐incompatible bone marrow transplants (BMTs). Density centrifugation or apheresis are used successfully at clinical scale. The advent of a bone marrow (BM) processing module for the Spectra Optia (Terumo BCT) provided the initiative to formally compare our standard technology, the COBE2991 (Ficoll, manual, "C") with the Spectra Optia BMP (apheresis, semiautomatic, "O"), the Sepax II NeatCell (Ficoll, automatic, "S"), the Miltenyi CliniMACS Prodigy density gradient separation system (Ficoll, automatic, "P"), and manual Ficoll ("M"). C and O handle larger product volumes than S, P, and M. STUDY DESIGN AND METHODS Technologies were assessed for RBC depletion, target cell (mononuclear cells [MNCs] for buffy coats [BCs], CD34+ cells for BM) recovery, and cost/labor. BC pools were simultaneously purged with C, O, S, and P; five to 18 BM samples were sequentially processed with C, O, S, and M. RESULTS Mean RBC removal with C was 97% (BCs) or 92% (BM). From both products, O removed 97%, and P, S, and M removed 99% of RBCs. MNC recovery from BC (98% C, 97% O, 65% P, 74% S) or CD34+ cell recovery from BM (92% C, 90% O, 67% S, 70% M) were best with C and O. Polymorphonuclear cells (PMNs) were depleted from BCs by P, S, and C, while O recovered 50% of PMNs. Time savings compared to C or M for all tested technologies are considerable. CONCLUSION All methods are in principle suitable and can be selected based on sample volume, available technology, and desired product specifications beyond RBC depletion and MNC and/or CD34+ cell recovery.